Membrane Contact Sites and Organelles Interaction in Plant Autophagy - Ye, Hao; Ji, Changyang; Guo, Rongfang; Jiang, Liwen (Frontiers in Plant Science, 2020)
Autophagy is an intracellular trafficking and degradation system for recycling of damaged organelles, mis-folded proteins and cytoplasmic constituents. Autophagy can be divided into non-selective autophagy and selective autophagy according to the cargo specification. Key to the process is the timely formation of the autophagosome, a double-membrane structure which is responsible for the delivery of damaged organelles and proteins to lysosomes or vacuoles for their turnover. Autophagosomes are formed by the closure of cup-shaped phagophore which depends on the proper communication with membrane contributors. The endoplasmic reticulum (ER) is a major membrane source for autophagosome biogenesis whereby the ER connects with phagophore through membrane contact sites (MCSs). MCSs are closely apposed domains between organelle membranes where lipids and signals are exchanged. Lipid transfer proteins (LTPs) are a large family of proteins including Oxysterol-binding protein related proteins (ORP) which can be found at MCSs and mediate lipid transfer in mammals and yeast. In addition, interaction between autophagosomes and other organelles can also be detected in selective autophagy for selection and degradation of various damaged organelles. Selective autophagy is mediated by the binding of a receptor or an adaptor between a cargo and an autophagosome. Here we summarize what we know about the MCS between autophagosomes and other organelles in eukaryotes. We then discuss progress in our understanding about ORPs at MCSs in plants and the underlying mechanisms of selective autophagy in plants with a focus on receptors/adaptors that are involved in the interaction of the autophagosome with other cytoplasmic constituents, including the Neighbor of BRCA1 gene 1 (NBR1), ATG8-interacting protein 1 (ATI1), Regulatory Particle Non-ATPase 10 (RPN10), and Dominant Suppressor of KAR2 (DSK2).